2009
DOI: 10.1055/s-0029-1224151
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Expression and its Association with Low-grade Inflammation in a Greek Population of Type 1 Diabetic Juveniles: Evidence for Differences in CD40 mRNA Isoforms Expressed by Peripheral Blood Mononuclear Cells

Abstract: Homeostatic dysregulation of CD40 and its association with inflammatory markers in T1DM patients, especially in those with poor glycaemic control, implies a pathophysiological role of CD40 in the low-grade inflammatory process in T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Subsequent investigations indicated that thromboembolic liabilities associated with anti-CD154 mAbs were a result of blocking interactions between CD154 and αIIbβ3. [34][35][36][37] This suggests that elevated CD40 receptor expression appears to be associated with a high elimination rate of anti-CD40 mAbs such as iscalimab. 26 These observations suggest that these events are inde- Consistent with preclinical data, iscalimab did not deplete peripheral leukocytes including B cells, and there were minimal effects on total serum IgM and IgG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent investigations indicated that thromboembolic liabilities associated with anti-CD154 mAbs were a result of blocking interactions between CD154 and αIIbβ3. [34][35][36][37] This suggests that elevated CD40 receptor expression appears to be associated with a high elimination rate of anti-CD40 mAbs such as iscalimab. 26 These observations suggest that these events are inde- Consistent with preclinical data, iscalimab did not deplete peripheral leukocytes including B cells, and there were minimal effects on total serum IgM and IgG.…”
Section: Discussionmentioning
confidence: 99%
“…33 Other data suggest that some patients with autoimmune disease displayed increased CD40 expression in target tissues and elevated serum/plasma soluble CD40 levels. [34][35][36][37] This suggests that elevated CD40 receptor expression appears to be associated with a high elimination rate of anti-CD40 mAbs such as iscalimab.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs were lysed according to the method of Chatzigeorgiou et al (2010) in 1% Triton (50 mmol/l Tris, pH 7.4, 150 mmol/l NaCl, 0.02% sodium azide and 1% Triton X-100) supplemented with a protease inhibitor cocktail (Sigma) for 30 min on ice. After centrifugation at 13 000 r.p.m.…”
Section: Preparation Of Cell Lysatesmentioning
confidence: 99%
“…Furthermore, although evidence suggests that hyperglycaemia affects negatively the development of albuminuria and progression of diabetic nephropathy [3] and also the results of De Muro et al support the existence of a strong influence of hyperglycaemia on GAGs metabolism [17,18], we (as Poplawska-Kita et al and Hansen et al) didn't find any correlation between GAGs levels and markers of glycaemic or metabolic control. On the other hand, we found significant correlations between urine GAGs and markers of inflammation such as CD40, a significant regulator of the low-grade inflammation in type 1 diabetes [19,20] and also MCP-1. These correlations indicate once again that low grade chronic inflammation is a factor of great importance for the initiation and progression of diabetic complications [21,22].…”
Section: Discussionmentioning
confidence: 73%